2016
DOI: 10.1615/critreveukaryotgeneexpr.2016015974
|View full text |Cite
|
Sign up to set email alerts
|

Recent Investigations for Discovery of Natural Antioxidants: A Comprehensive Review

Abstract: In the biological system, reactive oxygen species (ROS) play a crucial role in the defense mechanisms of the body. ROS is responsible for the initiation of several cellular responses that can impart the harmful effects on the body, initiating biomolecular damage. Therefore, it is essential to counteract the dangerous effects produced by ROS, which is only possible through the use of antioxidants. Researchers are evaluating medicinal plants to discover and investigate the new antioxidant sources. Using natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…However, high level of ROS could lead to male infertility. Many studies have demonstrated that antioxidants can reduce cellular ROS accumulation [17]. Semen ROS concentration was maintained at a lower level at the beginning of normal temperature storage, which is consistent with the results of Sutovsky's study [23].…”
Section: Discussionsupporting
confidence: 88%
“…However, high level of ROS could lead to male infertility. Many studies have demonstrated that antioxidants can reduce cellular ROS accumulation [17]. Semen ROS concentration was maintained at a lower level at the beginning of normal temperature storage, which is consistent with the results of Sutovsky's study [23].…”
Section: Discussionsupporting
confidence: 88%
“…2 By finding the natural resources and identification of the responsible compounds, new invention can be made for the treatment of this disease. 3 Genus Caesalpinia has been used for a very long time for the treatment of diabetes 17 but it was yet to be identified that which active agents are responsible for the cure of diabetes and by which mechanism the bioactive constituents showed activity against DM. One of the main reasons of DM is related to the damage of pancreatic β-cells.…”
Section: Ptp1b Inhibiting Capacitymentioning
confidence: 99%
“…Continued hyperglycemia due to DM causes varieties of dysfunctions and complications including renal disease, peripheral neuropathy, cardiovascular diseases, myocardial infarction, and non-healing foot ulcer. 1 There is growing evidence that reactive oxygen species (ROS) is the major cause of stimulating DM mechanisms 2,3 and responsible for the initiation of lipid peroxidation, enzyme deactivation, alteration in the collagen structure, and function. 3,4 In other words, we can say ROS have long term effects on the progression of diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it remains unclear whether oxidative stress is a major cause or merely a consequence of mitochondrial dysfunctions associated with AD [10], supplementation with antioxidants is reported to be beneficial especially in the early stages of the disease [11]. A variety of natural antioxidants have evolved in plants, including medicinal herb, to respond to natural oxygenic atmosphere [12]. Indeed, it has been well documented that various plantderived components, including phytoestrogen, possess their ability to reduce oxidative stress [13].…”
Section: Introductionmentioning
confidence: 99%